Revolutionizing Creativity: The Technical Infrastructure of AI-Driven Innovation - Ravi Sankar Susarla, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Integrating artificial intelligence into creative domains represents a transformative technological shift that enables unprecedented artistic expression and collaboration. This comprehensive exploration examines the infrastructure powering AI-driven creativity, from containerized algorithm environments to specialized model architectures optimized for creative applications. The technical foundation of these systems combines sophisticated cloud implementations leveraging AWS services with specialized DevOps practices tailored to the unique challenges of maintaining generative models. Performance optimization strategies address the critical requirements of creative workflows through model quantization, inference acceleration, and resource-efficient deployment patterns. The democratization of AI creativity tools has expanded access while raising important questions about authorship, originality, and creative authenticity. The evolution of these technologies demonstrates how purpose-built technical infrastructure can balance innovation with practical considerations of scale, security, and economic sustainability, ultimately reshaping how creative professionals approach their craft and expanding the boundaries of what creative expression can encompass.
Keywords: Artificial intelligence; creative infrastructure; model optimization; containerized deployment; generative systems; resource efficiency